1996
DOI: 10.1002/(sici)1097-4652(199608)168:2<239::aid-jcp2>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Changes in mitochondrial activity during avian myoblast differentiation: Influence of triiodothyronine or v-erbA expression

Abstract: Numerous data suggest that mitochondrial activity is involved in the regulation of cell growth and differentiation. Therefore, we have studied the changes in mitochondrial activity in avian myoblast cultures (QM7 line) undergoing differentiation or in BrdU-treated, differentiation-deficient cells. As we have previously shown that triiodothyronine and v-erb A expression stimulate myogenic differentiation, we have also observed their influence upon mitochondrial activity. Comparison of control and BrdU-treated m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
8
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 35 publications
4
8
0
Order By: Relevance
“…This observation clearly suggests that mitochondrial activity affects an important pathway involved in myoblast withdrawal from the cell cycle, an essential prerequisite for terminal differentiation. This result also provides new insight on our previous observations indicating that a sharp rise in mitochondrial activity occurs just before the onset of terminal differentiation (17). As this rise does not occur in differentiation-deficient myoblasts, the present data suggest that this event could take part in the induction of terminal differentiation.…”
Section: Mitochondrial Activity Affects Myoblast Differentiation By Isupporting
confidence: 85%
See 2 more Smart Citations
“…This observation clearly suggests that mitochondrial activity affects an important pathway involved in myoblast withdrawal from the cell cycle, an essential prerequisite for terminal differentiation. This result also provides new insight on our previous observations indicating that a sharp rise in mitochondrial activity occurs just before the onset of terminal differentiation (17). As this rise does not occur in differentiation-deficient myoblasts, the present data suggest that this event could take part in the induction of terminal differentiation.…”
Section: Mitochondrial Activity Affects Myoblast Differentiation By Isupporting
confidence: 85%
“…In an earlier work, we demonstrated that important changes in mitochondrial activity occurred during avian myoblast differentiation (17). In particular, high mitochondrial activity appears to be associated with the preliminary steps of myogenic differentiation, and its rise just before the onset of terminal differentiation could characterize the irreversible engagement of myoblasts in terminal differentiation.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…It is reported that high mt activity appears to be associated with the preliminary steps of avian myoblast differentiation, and its induction just before the onset of terminal differentiation could characterize an irreversible engagement in terminal differentiation (47,48). In line with this, we observed that HL-60RG cells treated with thiamphenicol, a specific inhibitor of mt translation, were unable to differentiate to monocyte/macrophage-like cells in response to TPA.…”
Section: Synthesis Of Mt Translation Factors Is Not Regulated At the supporting
confidence: 85%
“…These data shed new light on the sharp increase in mitochondrial activity spontaneously occurring just before myoblast differentiation, already proposed as a possible mechanism involved in the commitment of these cells in the differentiation programme (Rochard et al 1996). As we have recently observed a similar regulation of preadipocyte differentiation (A Fraysse, C WrutniakCabello, L Daury, A Rodier, F Casas, P Rochard, G Cabello & J Charrier, unpublished observations), this set of data demonstrates that, like the nuclear pathway, the direct mitochondrial T3 pathway is involved in the regulation of cell differentiation.…”
Section: Physiological Importance Of the Direct Mitochondrial T3 Pathwaymentioning
confidence: 56%